APLIKASI SIG UNTUK PENENTUAN DISTRIBUSI OPTIMAL RUANG TERBUKA HIJAU KOTA YOGYAKARTA - Ginting, Feber Antarius; Hartono, Hartono (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2017)
The aims of this research are: 1) to build city environment spatial database using GIS based on Quickbird Satellite Imagery interpretation, secondary data, and field data, 2) to make city green space optimal model based on city environmental spatial database, and 3) to apply the model in form of Yogyakarta City Green Space Optimal Map. Research method mainly consists of four steps, they are: 1) collecting primary data and secondary data, 2) building the database, 3) arrange city green space optimal model, and 4) apply the model. Primary data are Quickbird satellite imagery and field measurement, while the secondary data obtained from the related institutions. Parameters that were used to build city environment database are comfortable level, number and distance from traffic light, number and distance from main road intersection, the distance from main road, air and noise pollution of each land use category, qualitative of inhabitant oxygen necessity of each land use category, actual green space, and potential land for green space. The database consits of spatial data in vector format and attribute data in relational structure. Spatial model was built from three overlay methods in sequencial way : they are rating method, weighted rating method, and join spatial method. The results of the research are: 1) from the imagery can be produced Land Use, Road Network, Green Space, Potential Land for Green Space Maps with interpretation accuracy are 91.1%, 100%, 95.8%, and 94.8% respectively, 2) GIS procedure is able to build city environment spatial database and to perform a model of city green space optimal distribution, 3) The need of green space is 1022.9 ha, actual green space available is 94.87 ha, and potential land for green space in Yogyakarta city is 111.92 ha, 4) Distribution of the need of green space are along the main roads and its intersections. The areas cover along the roads of : 1) Adisucipto-Urip Sumoharjo– Sudirman–Diponegoro – Kyai Mojo–Godean streets (to city boundary), 2) Kusumanegara-Sultan Agung-Ahmad Dahlan–Wirobrajan–Martadinata streets (to city boundary), 3) Supeno-Sugiono–Sutoyo–M.T.Haryono–Sugeng Jeroni streets, 4) Magelang,-Herman Yohannes-Sutomo–Suryopranoto-Bausasran–Juminahan–Suryat majan–Gadjah Mada-Mataram–Suryotomo streets, 5) Cokroaminoto–Kapten Tandean–Bugisan (to city boundary), Suprapto–Wahid Hasyim–Bantul streets, and 6) Katamso–Parangtritis streets (to city boundary). Key words : Quickbird Imagery, Geographical Information System, Spatial Modelling, City Green Space Optimal Distribution